Study on the satisfaction among female UiTM students towards hostel facilities/ Mohd Omar Qaiyum Yahya, Yanti Yakop & Sheilla Sulrose Sulang - Yahya, Mohd Omar Qaiyum; Yakop, Yanti; Sulang, Sheilla Sulrose (2005)
Hostel is the one-life places that relates with student. Every school, institution or university has it own hostel. The management has provided the facilities for their students who stay in hostel. When all of the facilities can be used, it can create satisfaction among the students that used the facilities. The satisfaction of the student is not at the same level and because of this we outlined below our research or conduct a study about satisfaction of UiTM students towards hostel facilities.